2020
DOI: 10.1080/2374068x.2020.1751514
|View full text |Cite
|
Sign up to set email alerts
|

Solder joint failures under thermo-mechanical loading conditions – A review

Abstract: Solder joints play a critical role in electronic devices by providing electrical, mechanical and thermal interconnections. These miniature joints are also the weakest links in an electronic device. Under severe thermal and mechanical loadings, solder joints could fail in 'tensile fracture' due to stress overloading, 'fatigue failure' because of the application of cyclical stress and 'creep failure' due to a permanent long-term load. This paper reviews the literature on solder joint failures under thermo-mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Early creep modeling was carried out by separating the elastic and plastic deformation mechanisms. The creep, plastic, elastic, and other deformations were overlapped to form the creep [61,101], which is the main deformation failure mechanism of materials at high temperature. In particular, in microelectronic packaging, for example, for Sn-based lead-free solders, creep will occur when the operating temperature for the solder joint is 0.5 times more than the melting point of the solder [102].…”
Section: Creep Life Modelmentioning
confidence: 99%
“…Early creep modeling was carried out by separating the elastic and plastic deformation mechanisms. The creep, plastic, elastic, and other deformations were overlapped to form the creep [61,101], which is the main deformation failure mechanism of materials at high temperature. In particular, in microelectronic packaging, for example, for Sn-based lead-free solders, creep will occur when the operating temperature for the solder joint is 0.5 times more than the melting point of the solder [102].…”
Section: Creep Life Modelmentioning
confidence: 99%
“…In operating conditions, Mechatronic packages are subject to large temperature variations [10]. The coefficient of Thermal Expansion (CTE) mismatch between the various materials used in the package construction leads to thermomechanical stresses in solder joints, which can cause the damage in solder joints and consequently the failure of the entire package [11].…”
Section: Introductionmentioning
confidence: 99%
“…3,4,7,8 It has been shown that the density of the eutectic Sn-Bi alloy decreases with increasing temperature, and the thermal expansion characteristics of this alloy have been characterized. 9 While the thermal expansion characteristics of solder alloys are recognized as one of the factors that affect the reliability of electronic assemblies in service, 10 the coefficients of thermal expansion (CTE) of eutectic Sn-Bi used in modeling is typically a single value (e.g., 15 9 10 À6 /°C). 8 In service, the solder joints of electronic circuitry are exposed to temperature changes from the environment in which they operate or because of the heat generated by the functioning of the circuitry.…”
Section: Introductionmentioning
confidence: 99%